Topping up and the political support for social insurance - Andreas Bergh (Research Institute of Industrial Economics (IFN), 2013)
This paper analyzes how the possibility to complement social income insurance schemes with private insurance affects the political support for social insurance. It is shown that political support for social insurance is weakly decreasing in the replacement rate. Policy makers seeking to maintain support for social insurance schemes can do so by lowering the replacement rate and allowing topping up contracts. The strategy is likely to be a partial explanation for the continued political support for welfare states with universal social insurance schemes such as those in Scandinavia.
Keywords: H53; D72; 330; Social insurance; Topping up; redistribution